BF3·OEt2‐Promoted Tandem O‐Arylation/Hydroxylation: Efficient Synthesis of 2‐Hydroxyflavanones from Triazenylaryl‐Substituted Diketones. Issue 32 (25th September 2013) - Chen, Zhengkai; Yang, Weijun; Xu, Lijun; Zhang, Lili; Miao, Maozhong; Ren, Hongjun
Abstract: A transition‐metal‐free tandem O ‐arylation/hydroxylation approach has been developed for the efficient synthesis of highly substituted 2‐hydroxyflavanones from triazenylaryl‐substituted diketones. The intermediate benzopyrylium cation may be involved in these reactions. Abstract : Highly substituted 2‐hydroxyflavanones can be obtained through a tandem O ‐arylation/hydroxylation process from triazenylaryl‐substituted diketones in the presence of a Lewis acid.